Salivary metabolomics in oral cancer: A systematic review - Rita Antonelli; Giacomo Setti; Nathaniel S. Treister; Thelma A. Pertinhez; Elena Ferrari; Mariana Gallo; Ronell Bologna-Molina; Paolo Vescovi; Marco Meleti (Oral Oncology Reports)
Diagnosis of oral squamous cell carcinoma (OSCC) is frequently delayed, with most tumors being detected in advanced stages.Saliva may represent the ideal fluid for early detection of dysplastic and malignant oral lesions. Among available salivary analytical approaches (e.g., genomic, transcriptomic, proteomic), metabolomics appears promising in identifying the presence of small, specific molecules directly released from malignant cells that could potentially serve as diagnostic biomarkers.This systematic review evaluates the scientific evidence that supports the role of salivary metabolites in the early diagnosis of OSCC.Medline, Scopus and Web of Science databases were searched until February 2024. Two independent reviewers assessed the quality of the studies using a checklist proposed by the National Institutes of Health. They also assessed the level of evidence using the Oxford Center for Evidence-Based Medicine classification.Twenty-eight out of 9623 papers fulfilled the inclusion and exclusion criteria. The quality of the included papers ranged from “good” (n = 2), “intermediate” (n = 22), and “poor” (n = 4).Ten out of 25 studies evaluated one specific metabolite (sialic acid, cortisol, pyruvic acid, neopterine, 8-hydroxy-2-deoxyguanosine and malondialdehyde, endogenous porphyrin, among others), with the remainder analyzing a combination of 2 or more molecules. Overall, the presence and/or concentration of more than 100 salivary metabolites was investigated in association with histologically confirmed diagnosis of OSCC.All studies showed a statistically significant correlation between one or more metabolites and OSCC.These results suggest that metabolic analysis of saliva is a promising field for early diagnosis of OSCC, even though more well-conducted studies are needed.